Functional Analysis of Variants in Complement Factor I Identified in Age-Related Macular Degeneration and Atypical Hemolytic Uremic Syndrome - de Jong, Sarah; de Breuk, Anita; Bakker, Bjorn; Katti, Suresh; Hoyng, Carel B.; Nilsson, Sara C.; Blom, Anna M.; van den Heuvel, Lambert P.; den Hollander, Anneke I.; Volokhina, Elena B. (Frontiers in Immunology, 2022)
Complement factor I (FI) is a central inhibitor of the complement system, and impaired FI function increases complement activation, contributing to diseases such as age-related macular degeneration (AMD) and atypical hemolytic uremic syndrome (aHUS). Genetic variation in complement factor I (CFI) has been identified in both AMD and aHUS, with more than half of these variants leading to reduced FI secretion levels. For many of the variants with normal FI secretion, however, functional implications are not yet known. Here we studied 11 rare missense variants, with FI secretion levels comparable to wildtype, but a predicted damaging effects based on the Combined Annotation Dependent Depletion (CADD) score. Three variants (p.Pro50Ala, p.Arg339Gln, and p.Ser570Thr) were analyzed in plasma and serum samples of carriers affected by AMD. All 11 variants (nine for the first time in this study) were recombinantly expressed and the ability to degrade C3b was studied with the C3b degradation assay. The amount of degradation was determined by measuring the degradation product iC3b with ELISA. Eight of 11 (73%) mutant proteins (p.Pro50Ala, p.Arg339Gln, Ile340Thr, Gly342Glu, Gly349Arg, p.Arg474Gln, p.Gly487Cys, and p.Gly512Ser) showed significantly impaired C3b degradation, and were therefore classified as likely pathogenic. Our data indicate that genetic variants in CFI with a CADD score >20 are likely to affect FI function, and that monitoring iC3b in a degradation assay is a useful tool to establish the pathogenicity of CFI variants in functional studies.